2017
DOI: 10.1111/jth.13769
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of venous thromboembolism in Africa: a systematic review

Abstract: Background Venous thromboembolism (VTE) is among the three leading causes of cardiovascular disease worldwide. Despite its high burden, there has been no previous study summarizing the epidemiology of VTE in African populations. Hence, we conducted this systematic review to determine the prevalence, incidence and mortality associated with VTE, and to evaluate the use of VTE prophylaxis in Africa. Methods We searched PubMed, Scopus and African Journals Online to identify articles published on VTE in Africa from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 32 publications
3
70
0
Order By: Relevance
“…The high risk burden and low rates of adequate thrombo-prophylaxis for VTE in this semi-urban and rural hospitals is comparable to that reported in urban tertiary hospitals in Africa and beyond [9][10][11]18]. This is however associated with high rates of younger age groups, Table 3 shows the pre-admission and admission risk factors for VTE.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The high risk burden and low rates of adequate thrombo-prophylaxis for VTE in this semi-urban and rural hospitals is comparable to that reported in urban tertiary hospitals in Africa and beyond [9][10][11]18]. This is however associated with high rates of younger age groups, Table 3 shows the pre-admission and admission risk factors for VTE.…”
Section: Discussionsupporting
confidence: 64%
“…Besides the increase in the morbidity, the mortality is expected to be higher due to the low purchasing power of the patients, the poorly equiped hospitals (consumables, materials, and personnel), and poor health system (no health coverage). The exact burden of VTE is not known in this setting, as it may go undiagnosed and under-reported [11]. It is a disease condition that is largely underdiagnosed and under-treated despite the very high disease burden in hospitalized patients worldwide [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular diseases are the second commonest cause of premature disability and death in sub-Sahara Africa (SSA) [4][5][6]. A greater bulk of the burden of heart disease, kidney failure, stroke and premature death in this region is accounted for by hypertension [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Acute venous thromboembolism complicates one in 500-3000 pregnancies [1][2][3] and represents a leading cause of death among younger women in Western countries. [4][5][6][7] A recent analysis of medically certified vital registration data in Europe demonstrated that, despite an overall decreasing trend in age-standardized pulmonary embolism-related mortality, more than 1% of all deaths in younger women are due to pulmonary embolism.…”
Section: Introductionmentioning
confidence: 99%